A targeted approach significantly increases the identification rate of patients with undiagnosed haemochromatosis. - Cadet, E; Capron, D; Perez, A; Crépin, SN; Arlot, S; Ducroix, J; Dautréaux, M; Fardellone, P; Leflon, P; Merryweather-Clarke, A; Livesey, K; Pointon, J; et al. (2003)
OBJECTIVE: To determine the optimal means of identifying patients with undiagnosed haemochromatosis. DESIGN: Case-control study where cases are defined by the presence of specific clinical diagnoses or symptoms. SETTING: Primary care patients were recruited from three Oxfordshire practices and secondary care patients were recruited from those patients attending specialist clinics in Amiens University Hospital. SUBJECTS: A total of 569 patients recruited via hospital clinics and 60 primary care patients (recruited from 4022 consultations) presenting with the following haemochromatosis associated conditions, diabetes, arthralgia/chronic fatigue, osteoporosis or arthropathy were studied. The control group, a total of 991 healthy volunteers, were recruited through a Health Appraisal Centre. Patients and controls were included in the study if they or their family members had not previously been diagnosed with hereditary haemochromatosis. MAIN OUTCOME MEASURES: Serum ferritin concentration, transferrin saturation (Tsat) and presence of HFE mutations, C282Y and H63D. The check-up in controls consisted of a questionnaire, clinical examination, biochemical tests and screening for the presence of the C282Y and H63D mutations. RESULTS: Patient groups presenting with unstable diabetes or chronic fatigue and arthralgia together with a raised serum ferritin concentration showed an enrichment in the haemochromatosis-associated genotype HH/YY, odds ratio (OR) = 40.1, confidence interval (CI) = 8.0-202.1 and OR = 103, CI = 22.9-469.7, respectively. CONCLUSION: Patients presenting to hospital clinics with haemochromatosis associated conditions should be screened biochemically for iron overload. Only those with a serum ferritin >300 microg L-1 or Tsat >40% should subsequently go on to be genotyped for HFE mutations. The patients at greatest risk of having undiagnosed haemochromatosis are those presenting with unstable diabetes, or fatigue and/or arthralgia in the absence of any other explanation.